Coastal Flooding in the Balearic Islands During the Twenty-First Century Caused by Sea-Level Rise and Extreme Events - Luque, Pau; Gómez-Pujol, Lluís; Marcos, Marta; Orfila, Alejandro (Frontiers in Marine Science, 2021)
Sea-level rise induces a permanent loss of land with widespread ecological and economic impacts, most evident in urban and densely populated areas. Potential coastline retreat combined with waves and storm surges will result in more severe damages for coastal zones, especially over insular systems. In this paper, we quantify the effects of sea-level rise in terms of potential coastal flooding and potential beach erosion, along the coasts of the Balearic Islands (Western Mediterranean Sea), during the twenty-first century. We map projected flooded areas under two climate-change-driven mean sea-level rise scenarios (RCP4.5 and RCP8.5), together with the impact of an extreme event defined by the 100-year return level of joint storm surges and waves. We quantify shoreline retreat of sandy beaches forced by the sea-level rise (scenarios RCP4.5 and RCP8.5) and the continuous action of storm surges and waves (modeled by synthetic time series). We estimate touristic recreational services decrease of sandy beaches caused by the obtained shoreline retreat, in monetary terms. According to our calculations, permanent flooding by the end of our century will extend 7.8–27.7 km2 under the RCP4.5 scenario (mean sea-level rise between 32 and 80 cm by 2100), and up to 10.9–36.5 km2 under RCP8.5 (mean sea-level rise between 46 and 103 cm by 2100). Some beaches will lose more than 50% of their surface by the end of the century: 20–50% of them under RCP4.5 scenario and 25–60% under RCP8.5 one. Loss of touristic recreational services could represent a gross domestic product (GDP) loss up to 7.2% with respect to the 2019 GDP.